55‐1: Invited Paper: Yield and manufacturing challenges for microLED micro‐displays - Steudel, Soeren; Vertommen, Johan; Bach, Lars (SID International Symposium Digest of technical papers, 2024)
In this paper, we discuss microLED display yield and manufacturing challenges related to the CMOS integration as well as epi‐defectivity. Based on those considerations, we show the MICLEDI approach how to address them in a 300mm foundry compatible integration flow.